Analisis Korelasi Tingkat Pengetahuan Dan Sikap Dengan Kesiapsiagaan Bencana Banjir Pada Mahasiswa - Hery Prayitno; Hanifa Awalia (Jurnal Kesehatan, 2025)
Flooding is a disaster that often occurs in Indonesia, caused by both natural and non-natural factors. Floods disrupt life and threaten daily activities. In floods disaster management, nurses are required to have good knowledge and attitudes about floods preparedness. Good knowledge enables nurses to maintain positive attitudes to manage floods. This study aims to analyze the correlation between knowledge, attitudes, and flood preparedness. The study used quantitative correlation analysis with a cross-sectional design. There were 59 college students selected through random sampling. The instrument used was a questionnaire on knowledge, attitudes, and preparedness. Data was analyzed using the chi-square test. The results showed a significant relation between knowledge and preparedness (p-value=0.00), and no significant correlation between attitudes and preparedness (p-value=0.78). Based on these findings, students should seek ongoing disaster management training and updated resources to improve preparedness. Educational institutions should offer materials, workshops, or seminars to support preparedness and serve as reliable sources of information.